Trends in research on dietary behavior and cardiovascular disease from 2002 to 2022: a bibliometric analysis - Wang, Jie; Yu, Qingsong; Liu, Nannan; Nie, Kaidi; Sun, Xiaofang; Xia, Lina (Frontiers in Nutrition, 2023)
Abstract Background: Dietary behaviors and cardiovascular disease are two major health issues that have attracted a lot of attention from researchers worldwide. In this study, we aimed to provide a comprehensive analysis of the publication trends, authorship patterns, institutional affiliations, country/region contributions, journal outlets, highly cited documents, and keyword clusters in the field of dietary behaviors and cardiovascular disease research over the past two decades. Methods: We conducted a systematic literature review of peer-reviewed articles published from 2002 to 2022 in the Web of Science Core Collection database. We extracted and analyzed data on the annual publication volume, authorship patterns, institutional affiliations, country/region contributions, journal outlets, highly cited documents, and keyword clusters using bibliometric methods and visualization tools. Results: Our study analyzed 3,904 articles, including 702 reviews and 3,202 research articles. The results revealed a continuous increase in the number of publications in this field over the past two decades. The top 10 authors, institutions, and countries/regions with the highest publication output were identified, indicating the leading contributors to this field. Moreover, the most frequently cited documents and highly clustered keywords were identified, providing insights into the research themes and topics in this field. Conclusion: Our study provides a comprehensive analysis of the publication trends, authorship patterns, institutional affiliations, country/region contributions, journal outlets, highly cited documents, and keyword clusters in the field of dietary behaviors and cardiovascular disease research over the past two decades. The findings provide valuable information for researchers, policymakers, and stakeholders to understand the research landscape, identify research gaps, and develop future research directions in this field.